2010
DOI: 10.1590/s0103-90162010000100011
|View full text |Cite
|
Sign up to set email alerts
|

Fractal dimension and geostatistical parameters for soil microrelief as a function of cumulative precipitation

Abstract: Surface roughness is influenced by type and intensity of soil tillage among other factors, and it changes considerably with rain. In microrelief studies the advantages of using indices such as the fractal dimension, D, and the crossover length, l, is that they allow the partition of the roughness characteristics into properties that depend purely on the scale and on a scale free component, respectively. On the other hand, some geostatistical parameters may provide different ways to understand soil surface vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…agropec. bras., Brasília, v.53, n.6, p.756-764, June 2018 DOI: 10.1590/S0100-204X2018000600012 structural elements on soil surface (Vidal Vázquez et al, 2010b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…agropec. bras., Brasília, v.53, n.6, p.756-764, June 2018 DOI: 10.1590/S0100-204X2018000600012 structural elements on soil surface (Vidal Vázquez et al, 2010b).…”
Section: Resultsmentioning
confidence: 99%
“…Two fractal indexes -fractal dimension (D) and intersection distance (l) -were obtained according to Paz-Ferreiro et al (2008) and Vidal Vázquez et al (2010b). The fractal analysis was carried out using a variational method, assuming autosimilar surfaces to describe the microrelief.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatiotemporal variations of SSR and its evolution during rainfall events have been the focus of recent studies (Bertol et al, 2006;Bramorski, Maria, Silva, & Crestana, 2012;Haubrock, Kuhnert, Chabrillat, Güntner, & Kaufmann, 2009;Vázquez, Bertol, Siqueira, Paz-Ferreiro, & Dafonte, 2010;Zhang et al, 2015), and researchers studying tillage have examined the spatial heterogeneity of the surface microtopography, not just SSR (Vázquez, Vieira, Maria, & Paz González, 2010;Zhang, Zhao, Wang, & Wu, 2014). In this case, the findings have shown that the dynamic processes and mechanisms involved in run-off and erosion on a tilled surface limit the use of SSR alone.…”
mentioning
confidence: 99%
“…Abedini and Shaghaghian (2009) also found that surface detrending methods (e.g., linear, quadratic, and cubic fitting plane methods) had a minimal effect on D. Armstrong (1986) and Klinkenberg and Goodchild (1992) suggested that for fractal analysis of land surfaces, it is not necessary to remove the non-stationarity of the data in the semivariogram calculation since surface slope is a part of the topographic properties. However, Vázquez et al (2010) removed the slope of soil surface microrelief by finding a best fitting plane (linear, quadratic, or cubic fitting plane), and concluded that trend removal did affect the fractal indices (D and l). Thus, further studies are needed to evaluate the effect of surface trend removal on fractal analysis.…”
mentioning
confidence: 99%